Guardian of the sea : Jizo in Hawaiʻi - Clark, John R. K., 1946- (University of Hawai'i Press, 2007)
Jizo, one of the most beloved Buddhist deities in Japan, is known primarily as the guardian of children and travelers. In coastal areas, fishermen and swimmers also look to him for protection. Soon after their arrival in the late 1800s, issei (first-generation Japanese) shoreline fishermen began casting for ulua on Hawai'i's treacherous sea cliffs, where they risked being swept off the rocky ledges. In response to numerous drownings, Jizo statues were erected near dangerous fishing and swimming sites, including popular Bamboo Ridge, near the Blowhole in Hawai'i Kai; Kawaihapai Bay in Mokule'ia; and Kawailoa Beach in Hale'iwa. Guardian of the Sea tells the story of a compassionate group of men who raised these statues as a service to their communities. Written by an authority on Hawai'i's beaches and water safety, Guardian of the Sea shines a light on a little-known facet of Hawai'i's past. It incorporates valuable firsthand accounts taken from interviews with nisei (second-generation) fishermen and residents and articles from Japanese language newspapers dating as far back as the early 1900s. In addition to background information on Jizo as a guardian deity and historical details on Jizo statues in Hawai'i, the author discusses shorecasting techniques and organizations, which once played a key role in the lives of local Japanese. Although shorecasting today is done more for sport than subsistence, it remains an important ocean activity in the Islands. In examining Jizo and the lives of issei, Guardian of the Sea makes a significant contribution to our understanding of recent Hawai'i history.